2007
DOI: 10.1016/j.proci.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of secondary char oxidation in the transition from smoldering to flaming

Abstract: TitleThe role of secondary char oxidation in the transition from smoldering to flaming AbstractThe transition from forward smoldering to flaming in polyurethane foam is observed using indepth thermocouples and ultrasound probing. The experiments are conducted with small parallelepiped samples vertically placed in an upward wind tunnel. Three of the vertical sample sides are maintained at elevated temperature and the fourth is exposed to an upward oxidizer flow and a radiant heat flux. An ultrasound probing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…The experimental setup is a modification of that previously used to study the spontaneous transition from smoldering to flaming [9,10,12]. It consists of a vertically oriented foam sample heated on three of its surfaces with guard heaters and with the fourth, free surface, exposed to a parallel forced oxidizer flow and radiant heat flux.…”
Section: Experimental Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup is a modification of that previously used to study the spontaneous transition from smoldering to flaming [9,10,12]. It consists of a vertically oriented foam sample heated on three of its surfaces with guard heaters and with the fourth, free surface, exposed to a parallel forced oxidizer flow and radiant heat flux.…”
Section: Experimental Conceptmentioning
confidence: 99%
“…Several works have studied the spontaneous transition from smoldering to flaming, whereby the smolder reaction supplies the gaseous fuel and the heat to trigger a gas-phase ignition [8][9][10][11][12]. However, very little fundamental work has been done on the piloted ignition of the gaseous products of smoldering [13].…”
Section: Introductionmentioning
confidence: 99%
“…Putzeys et al [17] found that the smoulder velocity and peak temperature are strongly correlated to the occurrence of transition from smouldering to flaming. The transition has also been observed to occur when pores are formed in the region behind the smouldering front [18]. This implies that the smouldering front acts as the source of combustible vapours and heat for the flaming ignition.…”
mentioning
confidence: 99%
“…Smolder combustion has received considerable attention in the literature both experimentally [1]- [12] and computationally [13]- [30]. Experimental focus has ranged from studying smolder propagation to examining transition to flaming for various fuels.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism includes three pyrolysis reactions and four oxidation reactions. One of the oxidation reactions included is what has been referred to as "secondary char oxidation", which has been identified as the key step leading to transition to flaming [10], [12]. While the current focus is not to examine the transition from smoldering to flaming, the work establishes the framework to potentially do so in the future.…”
Section: Introductionmentioning
confidence: 99%